Penerapan Strategi Promosi Wisata Margasatwa Palembang Bird Park - Halim, Bobby; Windu Viatra, Aji; Ubaidillah, Muhammad; Amalia, Shalyna Nadya (UNIVERSITAS INDO GLOBAL MANDIRI, 2025)
This design project implements a promotional strategy through visual communication media for Palembang Bird Park to enhance its competitiveness and ensure cross-media consistency by applying the design thinking method (empathize, define, ideate, prototype, test). The work includes reorganizing the brand identity (a logo inspired by the Scarlet Macaw, typography, and color palette) as well as developing printed and digital promotional materials: a bird alphabet educational medium, posters, banners, animal information boards, and a wayfinding system. The design balances aesthetics, education, and branding to strengthen brand equity and enhance the visitor experience. With a cohesive visual strategy and a strong conservation narrative, this rebranding aims to increase brand awareness, expand promotional reach, and promote conservation-based tourism.